EVALUATION OF EFFECTIVENESS OF ANTIVIRAL THERAPY FOR CHRONIC HEPATITIS C, CAUSED BY HCV GENOTYPE 6 - D. A. Lioznov; N. H. Chung; S. L. Nikolaenko; T. B. Trung; F. T. Lan; N. D. Phong (Журнал инфектологии, 2017)
Objectives: Evaluating the effectiveness of 2 therapeutic schemes for chronic hepatitis C (genotype 6) which combined sofosbuvir and ribavirin, one of them also included pegylated interferon. Materials and methods: The study included 110 patients with chronic hepatitis C (genotype 6), who have undergone antiviral therapy (HTP) in Hepatology Clinic inHo Chi Minh City,Vietnamfrom November 2015 to July 2016. 24 patients were treated by Pegylated interferon alfa-2a, ribavirin and sofosbuvir for 12 weeks, 86 patients – by sofosbuvir and ribavirin for 24 weeks. Non-interferon regimen was administered primarily to patients with contraindications to the use of interferon. To monitor the effectiveness of antiviral therapy, quantification of HCV RNA in serum was performed by PCR prior to treatment, at 4th, 12th or 24th week (depending on the observation group) from the starting of treatment and at 12th, 24th week after completion of treatment. Results: All patients, who were treated with pegylated interferon, ribavirin and sofosbuvir, completed the full course of treatment and 100% of them are registered with sustained virological response at 12th and 24th week after the end of antiviral therapy (SVR-12 and SVR-24, respectively). In the group of patients, who treated with ribavirin and sofosbuvir, 97,7% of patients completed full course of treatment (SVR-12 was registered in 93% of patients, and SVR-24 – in 91,9% of patients). Of 75 patients without a history of HCC, SVR24 was registered in 74 people (98,7%), of 11 patients with HCC – in 5 patients (45,5%). SVR-24 was registered in 98% of patients with cirrhosis (F4) without HCC. Conclusion: The results can serve as a justification for the use of these schemes of antiviral therapy for special groups of patients and/or conditions when it is impossible to follow the latest recommendations, which will help to expand the access of patients to effective antiviral therapy for chronic hepatitis C.